Investigation on Reinforcement Effects of Nanocellulose on the Mechanical Properties, Water Absorption Capacity, Biodegradability, Optical Properties, and Thermal Stability of a Polyvinyl Alcohol Nanocomposite Film - Ebise Getacho Bacha; Hundessa Dessalegn Demsash; Lema Deme Shumi; Bune Erre Debesa (Advances in Polymer Technology)
This paper presents the reinforcement of nanocellulose (NC) in polyvinyl alcohol (PVA) to examine the effect of the amount of reinforcement on the properties of PVA. The nanocellulose was successfully extracted by sulfuric acid hydrolysis method and ultrasonication, and successively reinforced with polyvinyl alcohol by the solvent-casting method. After incorporating nanocellulose into the PVA matrix, the effect of nanocellulose on the tensile strength, elongation at break, water absorption capacity, transmittance, thermal stability, and biodegradability of PVA was investigated. The tensile strength increased from 24.5±0.53 MPa to 35.5±0.55 MPa and 40.6±0.73 MPa with the addition of 2%NC and 5%NC, respectively. The elongation at break increased from 40±0.53% to 45.7±0.53% with 2%NC, and after the reinforcement of 7%NC, it decreased to 32.2±0.75%. The water absorption capacity result reveals that neat PVA absorbs the highest amount of water which is 84.6±0.56% and is reduced to 73±0.78% by adding 2%NC. By increasing the nanocellulose loading to 7%, the water intake capacity was reduced to 61±0.59% which illustrates the water intake was reduced linearly with the increment of NC. The ultraviolet-visible (UV-Vis) result implies that the transmittance of neat PVA and PVA-2%NC composite film was 85.4% and 78.2% at 600 nm, respectively, which indicates the decrement in transmittance. The thermogravimetry analysis (TGA) reveals that the thermal stability of polyvinyl alcohol after incorporating nanocellulose particles was reduced. The weight loss of neat PVA is 70.7±1.7% after 90 days while the weight loss of the PVA composite films reinforced with 1%, 3%, 5%, 7%, and 9% was 65±1.85%, 57±1.57%, 55.6±0.64%, 52±1.73%, and 53.1±1.72%, respectively. The scanning electron microscopy micrograph for the PVA-6%NC nanocomposite film reveals a dispersion of nanocellulose in a matrix.